Sosialisasi dampak kecanduan penggunaan gadget bagi kehidupan anak sekolah di SMK kerta Cendekia Sidoarjo - Istiana, dina; Sulistyowati, Agus; Puji Lesrastari, Risti (Jurnal Pengabdian Kesehatan Masyarakat Mulawarman, 2025)
Activity ObjectivesThe purpose of this educational activity is to increase the knowledge of SMK Kerta Cendekia students about overcoming gadget addiction in adolescents. It is hoped that participants will be able to understand the dangers of gadget addiction and the impacts that occur from gadget addiction. Method Knowledge measurement using questionnaires was conducted twice, namely before counseling and after providing material. Filling out the questionnaire before counseling was carried out to determine the knowledge of participants before counseling. The questionnaire used was designed by the researcher and has been tested by experts according to their fields of science. The results, the minimum value of participant knowledge in the pretest was 60 with a maximum value of 80. The average pretest value of participants was 73.95 + 5.94. The table above also shows the minimum posttest value of 80 with a maximum value of 100. The average posttest value of participants was 90.26 + 7.88. The results of the statistical test showed that there was an increase in participant knowledge of the influence of gadgets on adolescents with an average pre and posttest value with a p-value <0.001